Glacial Geomorphology Between the Gran Campo Nevado and Estrecho de Magallanes, Chile (52–53°S, 73°W) - Herrera-Astudillo, G (Taylor and Francis Ltd., 2023)
We present the first extensive high-resolution glacial geomorphic map west of the Andean Cordillera in southernmost Chile (52.8–53.1°S, 73.0–73.9°W). The map extends over 1565 km2 and is based on high-resolution satellite images and aerial photographs. At selected locations, the remotely mapped geomorphology was corroborated by field observations. The study area is dominated by glacial erosional landforms (77%) over depositional landforms (23%), with published submarine depositional landforms having been included (e.g. moraines). Glacial drift, kettle kame topography and lateral and frontal moraines form the primary depositional landforms and sediment associations. Glacial cirques, wide U-shaped valleys, whalebacks, roches moutonnées and scoured bedrock characterize most of the mapped area. The spatial distribution of whalebacks and roches moutonnées in the study area indicates a lack of lithological control on their formation and a warm-based, dynamic ice velocity and thickness regime during Patagonian Ice Sheet cover and retreat during the last glacial cycle. © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group on behalf of Journal of Maps.